THE EFFECT OF DEPOSITION TECHNIQUE ON FORMATION OF TRANSPARENT CONDUCTIVE COATINGS OF SnO2 (Physical Sciences and Technology, 2022)
The producing technology of transparent conductive layers is the basis for many optoelectronic devices. To increase transparency and conductivity at low-cost and controlled methods is an important challenge. Studied samples of SnO2 coatings were obtained by sol-gel method. The deposition of films on glass substrates was carried out by dip coating, spin-coating and sprays-pyrolysis methods. According to micro-weighing, the film thickness varies from 250 nm to 290 nm. The layer with the most uniform thickness was achieved using spray pyrolysis. Films deposited by this technique exhibit the greatest transparency and lowest resistance. It is important to note that these samples have the minimum scatter of resistance values depending on the surface area. In case dip coating technique the resultant film contains open- and closed-type blisters. This confirms the fact of inhomogeneous surface morphology of these films. X-ray diffraction analysis showed that films obtained by spin-coating and dipping methods contain SnO2 crystallites, the size of which does not exceed 10.3 nm; while films obtained by spay pyrolysis are amorphous. This is because the formation of the structure in the spay pyrolysis proceeds faster due to the substrate heating.